Two‐Dimension Conjugated Acceptors Based on Benzodi(cyclopentadithiophene) Core with Thiophene‐Fused Ending Group for Efficient Polymer Solar Cells. Issue 5 (11th March 2020) - Zhang, Youdi; Cho, Yongjoon; Zhong, Lian; Wang, Ying; Huang, Bin; Yuan, Zhongyi; Yang, Changduk; Chen, Yiwang; Li, Yongfang
Abstract : The previously reported nonfullerene small molecule ITIC‐SF achieved via side chain tuning, promotes the power conversion efficiency of polymer solar cells (PSCs) with PBDB‐T‐SF as the donor from 10.1% and ITIC2 acceptors up to 12.2% for ITIC‐SF acceptors. To further this research, benzene end groups of molecules are herein substituted with thiophene rings, obtaining two new molecules BDTCH‐IC with alkylthio substituents, and BDTSF‐IC with alkylthio and fluorine substituents on their thiophene‐conjugated side chains. The absorption edges of BDTCH‐IC and BDTSF‐IC are red‐shifted to 824 and 793 nm, respectively. Strengthened molecular crystallinity, promoted charge extraction, and upgraded morphology endorse the advancement of photovoltaic performance of the small molecular acceptors. Using donor PM6, the two small molecule acceptors show good photovoltaic performance, although the highest occupied molecular orbit energy offsets are small between donor and acceptor materials. As a combination of side‐chain and end‐group engineering, the photovoltaic performance of the PSCs is increased to 13.1%, together with the best short‐circuit current ( J SC ) and fill factor reported thus far for this series of molecules. The results indicate that the modification of side chain and end groups is an effective way to improve the photovoltaic performance of small molecule acceptors. Abstract : Based on the previously reported acceptors ITIC2 and ITIC‐SF, using side chains and an end group strategy, a two‐dimension (2D) conjugated acceptor BDTSF‐IC is designed with fluorinated engineering and thiophene end group. The PM6:BDTSF‐IC‐based polymer solar cells achieve a photovoltaic performance of 13.1%, higher than those achieved by devices based on PM6:BDTCH‐IC (10.51%).